Strategic management plan for Davao City Water District-Employees Multipurpose Cooperative (DCWD-EMPC) - Maningo, Dennis A.; Digal, Larry N.; Concepcion, Sylvia B.; Gomez, Aurelia Luzviminda V. (Davao City School of Management, University of the Philippines Mindanao, 2008)
This policy and strategic management plan focuses on the Davao City Water District - Multipurpose Cooperative as the study?s subject organization. The DCWD-EMPC was organized in 1979 by a group of no less than 25 employees. A year after that it was registered as a credit cooperative. In 2000, the cooperative changed its status to multipurpose. It initially embarked in the supply of rice for DCWD employees? rice allowance benefits; photocopying services for DCWD customers; and selling of wet and dry goods. In 2007, it ventured into the messengerial business after the Department of Transportation and Communication approved its franchise application. The original intent of this business is to eater the bill handling operations of DCWD. The operation of their messengerial business resulted to net losses since it has started. The DCWD-EMPC profitability has been declining in the past two years. This paper will deal with the problem by utilizing the strategic planning framework developed by Fred David. This framework provides for an analysis of the external and internal conditions of the Cooperative. Opportunities and threats in the external environment were identified. Strengths and weaknesses were determined to assess the capability of the Cooperative to respond to the challenges in its external environments. This paper revisits the Cooperative?s VMG and affirms it. The strategic options designed to increase profitability were generated using the External Factor Evaluation (EFE) Matrix, Internal Factor Evaluation (IFE) Matrix and the SWOT Matrix. The most appropriate strategic option was then determined using the decision-making tool called Quantitative Strategic Planning Matrix (QSPM). The QSPM process revealed that the most suitable options for the Cooperative are (1) to concentrate on highly profitable businesses (2) institute a cost reduction program. The implementing programs are vital in achieving the objectives. They are considered as the action phase of this paper. It outlines what must be done by whom, when and how much resources to use. The full implementation of the strategy outlined in this paper will take five years, during which many changes may occur that can affect the strategy?s success. The control system designed in this paper will tract the strategy as it is being implemented. This ensures that issues and concerns are resolved before it becomes a crisis. This paper will utilize the Balance Scorecard Concept developed by Robert Kaplan of the Harvard Business School and David Norton of Renaissance School Incorporated (1996) in developing the Key Result Areas (KRA). The Performance Indicators (PI) then defines these key result areas specifically. It states the performance standards to which the KRAs will be evaluated.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, December 2008.
Keywords: Strategic plan